New records for the herpetofauna of Lima, description of Telmatobius rimac Schmidt, 1954 tadpole (Anura: Ceratophrydae) and a key to the amphibians - Aguilar, César (2007)
The tadpole of Telmatobius rimac is described and eight species of amphibians and reptiles are reported for the first time in Departamento de Lima. New amphibians records are Gastrotheca peruana and Pleurodema marmorata. New reptile records are the lizards Phyllodactylus gerrophygus and Ameiva edracantha, and the snakes Leptotyphlops tricolor, Philodryas tachymenoides, Sibynomorphus vagus and Tantilla capistrata. With this study, the herpetofauna of Lima is composed of 7 amphibians and 33 reptiles. An identification key for amphibians and an updated list of the herpetofauna for Departamento de Lima is provided.